2016
DOI: 10.1111/bju.13666
|View full text |Cite
|
Sign up to set email alerts
|

24‐month durability after crossover to the prostatic urethral lift from randomised, blinded sham

Abstract: The PUL procedure is associated with rapid symptom relief, increased urinary flow rate and QoL improvement that remain stable over 24 months. Morbidity is low and sexual function is preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 23 publications
5
36
0
Order By: Relevance
“…The Sham cohort in this trial were unblinded at 3 months, and 80% (n=53) were enrolled in a separate Crossover Study, with subjects serving as their own control. These results were reported after 12 and 24 months (13,14). The 48-month results from the original cohort randomised to UroLift in the LIFT study have recently been published (4).…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…The Sham cohort in this trial were unblinded at 3 months, and 80% (n=53) were enrolled in a separate Crossover Study, with subjects serving as their own control. These results were reported after 12 and 24 months (13,14). The 48-month results from the original cohort randomised to UroLift in the LIFT study have recently been published (4).…”
Section: Introductionsupporting
confidence: 57%
“…Rukstalis and colleagues [2016] reported on the 24-month durability of responses to the individual domains in IPSS in a relatively unique cohort—men acting as their own controls who had been originally randomised to the sham arm of the LIFT study, formally assessed and then assessed again after unblinding and treatment with the PUL procedure (14). The results of this study showed that although both irritative and obstructive symptoms initially improve after the sham procedure the improvement in the obstructive domains decreases after three months, whereas the response in the same subjects after the UroLift procedure is significantly better and sustained (14). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from ease‐of‐use, which has been re‐confirmed by this study, the issues that remain of interest include durability, ejaculatory function, overall cost, and morbidity. Although durability looked poor initially with an ~20% retreatment rate at 2 years , this seems to have improved to ~10% in this and other series with more experience . However, case selection probably played a significant part in this reduction, as patients with retention, median lobes and post‐void residual urine (PVR) values of >250 mL were excluded.…”
mentioning
confidence: 69%